Agroindustri Gula Merah Tebu : Analisis Produksi, Pemasaran, dan Dampaknya Terhadap Lingkungan Pada Usaha Haeruddin di Kabupaten Bone - Andi Anna Maemunah; Ummy Qalsum; Muh.Haidir Hakim; Aditya Arief Rachmadhan (Jurnal Informasi, Sains dan Teknologi, 2025)
This study aims to analyze the production process, marketing strategies, and environmental impacts of sugarcane brown sugar agroindustry at the household scale, using the Haeruddin enterprise located in Latellang Village, Patimpeng District, Bone Regency as a case study. A descriptive qualitative approach was employed, with data collected through in-depth interviews, participatory observation, and document analysis. The results show that the enterprise manages approximately 50 hectares of sugarcane land with productivity ranging from 30–60 tons per hectare, which is below the national average. The production capacity reaches 1–2 tons of sugarcane per day, producing approximately 1 ton of brown sugar daily, and involves local labor in cultivation and processing activities. Marketing is conducted through direct sales and local distributors, with prices ranging from IDR 8,000–10,000 per kilogram, without the use of digital promotion or modern retail channels. From an environmental perspective, the production process generates solid, liquid, and gaseous waste; however, solid waste in the form of bagasse is reused as fuel, while liquid waste and combustion residues are only partially managed. These findings indicate that while the enterprise contributes to employment and the local rural economy, improvements in production efficiency, marketing strategies, and environmental management are required to enhance competitiveness and sustainability. This study provides practical insights for the development of sustainable household-scale sugarcane brown sugar agroindustries in rural areas.